A5 noradrenergic‐projecting C1 neurons activate sympathetic and breathing outputs in anaesthetized rats. Issue 2 (7th December 2021) - Malheiros‐Lima, Milene R.; Silva, Talita M.; Takakura, Ana C.; Moreira, Thiago S.
Abstract : New Findings: What is the central question of this study? C1 neurons innervate pontine noradrenergic cell groups, including the A5 region: do A5 noradrenergic neurons contribute to the activation of sympathetic and respiratory responses produced by selective activation of the C1 group of neurons. What is the main finding and its importance? The increase in sympathetic and respiratory activities elicited by selective stimulation of C1 neurons is reduced after blockade of excitatory amino acid within the A5 region, suggesting that the C1–A5 pathway might be important for sympathetic‐respiratory control. Abstract: Adrenergic C1 neurons innervate and excite pontine noradrenergic cell groups, including the ventrolateral pontine noradrenergic region (A5). Here, we tested the hypothesis that C1 activates A5 neurons through the release of glutamate and this effect is important for sympathetic and respiratory control. Using selective tools, we restricted the expression of channelrhodopsin2 under the control of the artificial promoter PRSx8 to C1 neurons (69%). Transduced catecholaminergic terminals within the A5 region are in contact with noradrenergic A5 neurons and the C1 terminals within the A5 region are predominantly glutamatergic. In a different group of animals, we performed retrograde lesion of C1 adrenergic neurons projecting to the A5 region with unilateral injection of the immunotoxin anti‐dopamine β‐hydroxylase‐saporin (anti‐DβH‐SAP) directly into the A5 region during the hypoxic condition. As expected, hypoxia (8% O2, 3 h) induced a robust increase in fos expression within the catecholaminergic C1 and A5 regions of the brainstem. Depletion of C1 cells projecting to the A5 regions reduced fos immunoreactivity induced by hypoxia within the C1 region. Physiological experiments showed that bilateral injection of kynurenic acid (100 mM) into the A5 region reduced the rise in mean arterial pressure, and sympathetic and phrenic nerve activities produced by optogenetic stimulation of C1 cells. In conclusion, the C1 neurons activate the ventrolateral pontine noradrenergic neurons (A5 region) possibly via the release of glutamate and might be important for sympathetic and respiratory outputs in anaesthetized rats.